SURVEY KE,illAAN GIZI DAN TINGKAT KESEGARAN JASMANI SISWA SEKOLAH DASAR DI DAERAH ISTIMEWA YOGYAKARTA - Suharjana, Suharjana (Jurnal Cakrawala Pendidikan, 2016)
This article is based on a research whose objective was to investigate the nutritional state and physical fitness of elementary school children. For that a survey employing tests and measurements on a sample of over 500 children obtained through quota random sampling from a population offourth, fifth, and sixth graders at state elementary schools’ in the Yogyakarta Special Province was conducted. Their nutritional state was established by means of the Davenport-Koup formula (Hasnan Said, 1979)and measurement standard by Sarjono (I 992) while their physical fitness was determined by means of theTKJI (Tes Kesegaran Jasmani Indonesia or Indonesian Physical Fitness Test) of 1999. The data were analyzed descriptively using percentages. The results show that 2670r 51.4 % ofthese children are in their nutritional state categorized good, with 51 or 10.2 % of this group categorized fat and the remaining 2I6 or 4 1.2 % categorized normal, while 294 or 48.6 % of the sample group are categorized suffering malnutrition, with 47 or 9.4 % of them categorized very fat (or overweight), 184 or 36.8 % of them categorized thin, and 12 or 2.4 % of them categorized very thin (or. nutritionally deficit or undernourished). Meanwhile, most of the children in the sample, 312 or 62.4 % ofthem, are categorized bad in physical fitness, with 278